1982
DOI: 10.1128/jb.152.1.166-174.1982
|View full text |Cite
|
Sign up to set email alerts
|

Transformation-deficient mutants of Bacillus subtilis impaired in competence-specific nuclease activities

Abstract: A comparison of the nucleolytic activities in competent and physiologically low-competent wild-type cultures of Bacillus subtilis in DNA-containing sodium dodecyl sulfate-polyacrylamide gels revealed the existence of three competence-associated nuclease activities with apparent molecular weights of 13,000, 15,000, and 26,000. The three activities, which were dependent on manganese or magnesium ions, were specifically present in the competent fraction of a competent culture. The competence-associated nucleolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Conceivably, subunit a might be involved in binding, because it is the polypeptide lacking in binding-deficient mutants (23), and the nuclease subunit b, which is present in these mutants, might be involved in DNA entry. The idea of a protein complex involved in both binding and entry of donor DNA in B. subtilis was strongly supported by more recent experiments (submitted for publication), which indicated that subunit b was in fact the nuclease that is absent in DNA entry-deficient mutants of B. subtilis (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conceivably, subunit a might be involved in binding, because it is the polypeptide lacking in binding-deficient mutants (23), and the nuclease subunit b, which is present in these mutants, might be involved in DNA entry. The idea of a protein complex involved in both binding and entry of donor DNA in B. subtilis was strongly supported by more recent experiments (submitted for publication), which indicated that subunit b was in fact the nuclease that is absent in DNA entry-deficient mutants of B. subtilis (18).…”
Section: Discussionmentioning
confidence: 99%
“…In Diplococcus pneumoniae binding to competent cells seems to result in the introduction of single-stranded nicks in the donor DNA (11,12). In addition, in both D. pneumoniae and B. subtilis nuclease activity seems to be required for entry of bound DNA (13,18). It was of interest to study whether the purified DNA-binding protein complex exhibited nuclease activity.…”
Section: --mentioning
confidence: 99%
See 1 more Smart Citation